Revolutionizing Workplace Safety Through Innovative Ergonomic Solutions in Indonesia: Merevolusi Keselamatan di Tempat Kerja Melalui Solusi Ergonomis yang Inovatif di Indonesia - Putri, Natasya Kurniawan; Putra, Boy Isma (Indonesian Journal of Law and Economics Review, 2024)
General Background: Workplace accidents significantly impact employee health, productivity, and organizational efficiency, necessitating effective safety and health management strategies. Specific Background: The study investigates the use of the Macro Ergonomic Analysis and Design (MEAD) method at PT Esprobags to improve occupational health and safety measures. Knowledge Gap: PT Esprobags faces challenges in effectively addressing employee health concerns, especially regarding health insurance and workplace conditions, despite increasing demand for safety protocols. Aims: This research aims to identify key health and safety issues affecting employees, utilizing MEAD to analyze and design solutions that mitigate workplace accidents and improve overall employee well-being. Results: The findings indicate that inadequate health insurance and infrequent health checks, along with insufficient drinking water quality and room cleanliness, are primary concerns among employees. The analysis reveals that environmental factors significantly influence employee safety, health, and performance, contributing to a 60.7% variance in the work environment's impact on safety and performance. Novelty: This study introduces a structured ergonomic approach tailored to the unique needs of the manufacturing sector, emphasizing the importance of holistic workplace assessments. Implications: PT Esprobags' implementation of the MEAD methodology can improve employee satisfaction, productivity, and safety, contributing to a broader understanding of workplace ergonomics and occupational health. Highlights: Health Concerns: Inadequate health insurance and checks impact employee well-being. Environmental Impact: Workplace conditions significantly affect safety and productivity. Implementation Benefits: MEAD enhances satisfaction and reduces workplace accidents. Keywords: workplace safety, ergonomic analysis, employee health, Macro Ergonomic Analysis and Design, occupational safety